WHEN DOES CSR AND INSTITUTIONAL OWNERSHIP CREATE VALUE? : (The Moderating Role of Financial Performance) - Siti Nur Hidayati; Muhammad Ja'far Shodiq (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2026)
Introduction: Firm value has become a critical indicator of corporate sustainability and investor confidence, particularly in the basic materials sector, where business operations generate substantial environmental and social impacts. Despite extensive research, empirical findings regarding the effects of Corporate Social Responsibility (CSR) and institutional ownership on firm value remain inconclusive. This study investigates these relationships by examining the moderating role of financial performance while controlling for firm size. Method: This study employed a quantitative research design using secondary data collected from the annual and sustainability reports of manufacturing firms in the basic materials sector listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Using purposive sampling, 80 firm-year observations were selected. The hypotheses were tested using Moderated Regression Analysis (MRA). Results: The findings indicate that CSR, institutional ownership, and firm size do not have a significant direct effect on firm value. However, financial performance significantly strengthens the relationship between CSR and firm value, whereas it does not moderate the relationship between institutional ownership and firm value. Discussion: These findings suggest that CSR contributes to firm value only when supported by strong financial performance. Conversely, institutional ownership alone is insufficient to enhance firm value, regardless of the firm's financial performance. This study enriches the literature on CSR, corporate governance, and firm value by providing evidence from Indonesia's basic materials sector and offers practical implications for managers and policymakers in promoting sustainable corporate practices and strengthening good corporate governance.